A method for determining calcium ion content in lime powder
By adjusting the powder amount of lime powder detection sample and eliminating sample cracks, the problem of lime powder detection sample prone to cracks in the prior art is solved, and the accuracy and stability of X-fluorescence spectroscopy detection are achieved.
Patent Information
- Application Number
- CN202411940426.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, lime powder detection samples are prone to surface cracks during the sample preparation process, which affects the accuracy of the detection.
By adjusting the powder usage of the pressed sample, gradually reduce the weight of the lime powder to be tested and pressed until no cracks occur, determine the powder usage without cracks, and prepare the calibration sample according to the same method, correct the calibration parameter value in the detection system, and perform X-fluorescence spectroscopy detection.
The cracks in the sample are eliminated, the accuracy of X-fluorescence spectroscopy detection is ensured, the calcium ion content of lime powder samples with different properties can be accurately measured, and the adjustment amplitude of calibration parameter values in the system is reduced.
Smart Images

Figure CN119757434A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical analysis and detection, and in particular to a method for determining the content of calcium ions in lime powder. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In the X-ray fluorescence spectrum detection method, the sample is irradiated by the excitation light source to produce characteristic X-rays of specific elements (i.e. X-ray fluorescence), which are collected by the detector and converted into electrical pulse signals. After separation, they are recorded by the corresponding element channel. When the intensity of the excitation light source remains unchanged, the more atoms in the sample, the greater the probability of producing the corresponding characteristic X-rays, and thus the greater the counting result (i.e. counting rate) of the corresponding element channel. Therefore, the channel counting rate is directly proportional to the number of corresponding elements in the unit volume of the sample, that is, the concentration of the element.
[0004] In the field of electricity and heat, it is necessary to accurately measure the content of calcium ions in lime powder to provide key data support for optimizing production processes and controlling product quality. However, in the existing technology, lime powder test samples are prone to surface cracks during the sample preparation process, which affects the accuracy of the test. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for determining the calcium ion content in lime powder, establish an experimental analysis method, increase the inspection capability, and provide accurate data for the device to guide production. In order to achieve the above object, the present invention is implemented through the following technical solutions: A method for determining the calcium ion content in lime powder, comprising the steps of: S1, preparing lime powder to be tested with set fineness; S2, use lime powder to be detected to suppress the sample, when cracks occur, gradually reduce the weight of lime powder to be detected for sample preparation and test compression, until the test compression does not produce cracks for many times, the powder consumption that does not produce cracks is determined as the weighing weight of powder to be detected, and the lime powder used to determine the calcium ion concentration is used to prepare the calibration sample in the same way; S3, correcting the calibration parameter values in the detection system, and performing X-ray fluorescence spectrum detection on the sample; S4. Compare the X-ray fluorescence spectrum detection result of the sample with the X-ray fluorescence spectrum detection result of the calibration sample to obtain the calcium ion content in the sample.
[0006] Optionally, in S1, the fineness of the lime powder is 0.08 mm square hole sieve and more than 90% of it passes through the sieve.
[0007] Optionally, in S2, the pressure of the pressed sample is a set value, and the pressure of the pressed sample of the lime powder to be tested is the same as the pressure of the calibration sample.
[0008] Optionally, in S2, the method of reducing the weight of lime powder used for sample preparation for test pressing is: every time the amount of lime powder is reduced by 0.08~0.1g, test pressing is performed 5~6 times.
[0009] Optionally, in S2, the criterion for judging whether cracks are not generated is that the pressed sample does not protrude from the end face of the steel ring, the sample is removed after pressing, and after the floating powder of the sample is blown off, the tested surface and the back face are flat and free of cracks.
[0010] Optionally, in S4, the powder fineness of the calibration sample is the same as that of the lime powder.
[0011] Optionally, in S4, the weight of the calibration sample is consistent with the weighed weight of the powder to be tested.
[0012] Optionally, in S4, the difference between two calcium ion content results repeatedly measured by the same operator for the same batch of lime powder to be tested is not greater than 10% of their arithmetic mean.
[0013] The beneficial effects of the present invention are as follows: The present invention eliminates cracks in the sample by adjusting the amount of powder used to press the sample. (When the SH-3 tablet press is used to press the sample, if the size of the tablet press tool is fixed and the sample is pressed to the same thickness, the smaller the powder mass, the smaller the actual pressure, and this reduction will not affect the test result. In this way, a test sample without cracks is prepared, and the accuracy of the X-ray fluorescence spectrum can be guaranteed. Then, the b value is corrected to eliminate the difference between the sample preparation of the powder to be tested and the sample preparation of the calibration sample, so that the method can be applied to the accurate calcium ion content of lime powder samples with different properties, and the adjustment range of the calibration parameter value in the system can be minimized under the premise that the sample is not cracked. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0015] Figure 1 This is a schematic diagram of the process of using a mold to press a sample in Example 1; Figure 2 Schematic diagram of a crack-free sample in Example 2; Figure 3 Schematic diagram of a cracked sample in Example 2.
[0016] Among them, 1. die rod; 2. lime powder to be tested; 3. die ring; 4. sample ring; 5. die pad; 6. test sample. DETAILED DESCRIPTION
[0017] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0018] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0019] A specific embodiment of the present invention provides a method for determining the calcium ion content in lime powder, the steps comprising: S1, preparing lime powder to be tested with set fineness; S2, use lime powder to be detected to suppress the sample, when cracks occur, gradually reduce the weight of lime powder to be detected for sample preparation and test compression, until the test compression does not produce cracks for many times, the powder consumption that does not produce cracks is determined as the weighing weight of powder to be detected, and the lime powder used to determine the calcium ion concentration is used to prepare the calibration sample in the same way; S3, correcting the calibration parameter values in the detection system and performing X-ray fluorescence spectrum detection on the sample; S4. Compare the X-ray fluorescence spectrum detection result of the sample with the X-ray fluorescence spectrum detection result of the calibration sample to obtain the calcium ion content in the sample.
[0020] In the above process, the SH-3 tablet press is used. Since the size of the tablet pressing tool is fixed, the smaller the mass of the raw material powder, the smaller the pressure is for the same thickness of the test piece, thereby achieving a slight adjustment of the pressure, which can eliminate cracks without significantly affecting the test results.
[0021] Optionally, in S1, the main source of lime powder is natural limestone, which is obtained by crushing and grinding; the chemical composition of limestone powder is mainly CaCO3; the production process of limestone powder can also utilize waste materials such as limestone chips and stone powder generated in the production process of machine-made sand and gravel; the main use of lime powder in power plants is as a desulfurizer to help reduce sulfur dioxide (SO2) emissions generated in the process of thermal power generation. In addition to desulfurization, limestone also participates in the denitrification and dust removal processes of flue gas; although the effect of direct use in denitrification is limited, the denitrification efficiency can be indirectly improved through synergistic action with a denitrification catalyst.
[0022] Optionally, in S1, the fineness of the lime powder is more than 90% passing through a 0.08 mm square hole sieve; when the sample particles are large, the photons of the excitation light source are not easy to cause the sample to generate X-rays, but when the particles are smaller than 0.1 mm, the measurement results are independent of the particle size; the national standard requires that the fineness of cement raw materials in the calcination process is more than 90% passing through a 0.08 mm square hole sieve. In the fields of electricity and heat, the measured samples only need to meet this fineness requirement without considering the impact of the fineness on the measurement results; when the fineness cannot meet the national standard requirements, the instrument indication will be low. At this time, the operator must grind it manually and then press the sample to obtain the correct measurement result.
[0023] Optionally, in S2, the pressure of the pressed sample is 25MPa, which is determined by the pressure requirement of the tablet press, and the pressure of the lime powder pressed sample to be tested is the same as that of the calibration sample; since the formed test sample needs to have sufficient mechanical strength, the thickness of the sheet sample after forming is about 3.5~4mm as required, and the atoms that can be hit by the excitation light source are only within the thickness range of about 0.2mm on the surface of the test surface of the sample. Therefore, the measurement result is not related to the thickness (ie weight) of the sample when the material is evenly distributed, but only to the density (guaranteed by the pressure of the sample pressing).
[0024] Optionally, in S2, when the sample does not crack, increasing the pressing pressure as much as possible helps to reduce the impact of changes in density and thickness of the sample matrix on the accuracy of the measurement results.
[0025] Optionally, in S2, the method of reducing the weight of lime powder used for sample preparation for trial pressing is: every time the amount of lime powder is reduced by 0.08~0.1g, trial pressing is performed 5~6 times. When the size of the tablet pressing tool of the selected SH-3 tablet press is fixed, the smaller the raw material mass, the smaller the pressure used for pressing to the same thickness; under the condition of standardized sample pressing process, the low moisture content and coarse fineness of the batch of samples are the causes of cracks, but the moisture adjustment is time-consuming, the grinding process is prone to cause component loss, and the difference between different personnel may be large, which is not conducive to the formulation of operating specifications. The method of gradually reducing the raw material mass by a small amount can achieve standardized operation, thereby improving the stability of measurement results of different batches and different personnel.
[0026] Optionally, in S2, the criterion for whether cracks are not generated is: the pressed sample does not protrude from the end face of the steel ring; after pressing, the sample is removed and the loose powder is blown off; and the tested surface and the back are carefully checked to be flat and free of cracks.
[0027] Optionally, in S3, when using the SH-3 tablet press, the calibration parameter value in the system is the b value, which is a constant determined by a large number of calibration processes and is used to correct the systematic error in the measurement process to ensure the accuracy of the measurement results; during the X-ray fluorescence spectrum detection process, the calculation formula for the detection ion content can be obtained by calculating the ratio between the counting rate of the sample and the counting rate of the hard sample; in this calculation formula, b is a constant determined by a large number of calibrations.
[0028] Optionally, in S4, the powder fineness of the calibration sample is the same as that of the lime powder.
[0029] Optionally, in S4, the difference between two calcium ion content results repeatedly measured by the same operator for the same batch of lime powder to be tested is not greater than 10% of their arithmetic mean.
[0030] Optionally, during the measurement, a high pressure is selected without the sample cracking.
[0031] Example 1 Determination of calcium ion content in lime powder. The mold for pressing the sample is as follows: Figure 1 As shown, it includes a die rod 1, a die ring 3, a sample ring 4 and a die pad 5. The cavity formed by the die ring 3 and the sample ring 4 is used to accommodate the relatively loose lime powder 2 to be detected before pressing. The die rod 1 is used to apply a set pressure to the loose lime powder 2 to be detected in the cavity. The sample ring 4 is used to accommodate the compacted sample 6 after pressing. The die pad 5 is used to form a flat detection surface. After pressing, the compacted sample 6 is loaded in the sample ring 4. The thickness of the sample 6 is less than the height of the sample ring 4, so that the thickness of the sample 6 can be adjusted within a certain range. The die pad 5 ensures that the sample 6 is flush with the surface of the sample ring 4 for detection in the X-ray fluorescence spectrum detection equipment.
[0032] The inner diameters of the die ring 3 and the sample ring 4 are 4 cm, the height of the sample ring 4 is 8 mm, the height of the die ring is 2.2 cm, and the weight of the lime powder used to prepare the sample 6 is about 10-12 g.
[0033] When pressing the sample, Figure 1As shown: first place the sample ring 4 on the die pad 5, and then install the die ring 3 above the sample ring 4; weigh about 10.5g of powder and pour it into the cavity, scrape the powder flat with a stirrer, then slowly put the die rod 1 into the die ring 3 to make it fall, and then hold the die ring 3 with your hand to rotate the die rod 1 to make the powder filled evenly; move the device with the sample loaded to the visual center position of the tablet press workbench, pull the handle, apply pressure to the die rod 1, maintain the pressure for 5 to 10 seconds, then pull the handle to the starting position, and take out the squeezed device; the operator presses the die ring 3 with one hand and rotates the die rod 1 with the other hand to separate the die rod 1 from the back of the sample 6, then removes the die ring 3, the die rod 1 and the die pad 5, and the remaining sample ring 4 and the sample 6 fixed by the sample ring 4, use an ear bulb to blow away the floating powder on the upper and lower surfaces of the sample 6 to obtain the sample to be tested.
[0034] When using the SH-3 tablet press, since the size of the tablet pressing tool is fixed, when obtaining a sample of set thickness, the smaller the mass, the smaller the pressure used, and vice versa.
[0035] The steps include: S1. Prepare lime powder to be tested with a set fineness. The powder sample to be tested comes from purchased natural limestone. The lime powder is obtained by crushing and grinding the rock.
[0036] S2, use lime powder to be detected to compress the sample, first weigh 10.5g of sample for compression, the compression pressure is 25MPa, when the prepared sample cracks, reduce the weighing of 0.1g sample (i.e., use 10.4g sample), according to the same compression pressure, test the pressure, detect whether there are cracks on the surface of the test pressure sample, and repeat the preparation of 5 test pressure samples; if any one of the 5 samples has cracks, further reduce the weighing of 0.1 product for test pressure (i.e., use 10.3g sample), detect whether there are cracks on the surface of the test pressure sample, repeat the preparation of 5 test pressure samples, and circulate the operation until the sample that has been tested for 5 times does not produce cracks, and the amount of powder that does not produce cracks is determined as the weighing weight of the powder to be detected (10.2g in the present embodiment); in the same way, a calibration sample is prepared using lime powder for determining the calcium ion concentration, and the calibration sample is consistent with the weighing weight of the powder to be detected; S3. Correct the b value in the detection process and conduct X-ray fluorescence spectrum detection on the sample. The b value is used to correct the systematic error in the measurement process to ensure the accuracy of the measurement result. The content calculation formula can be obtained by calculating the ratio between the counting rate of the sample and the counting rate of the hard sample. In this calculation formula, b is a constant determined by a large number of calibrations.
[0037] S4. Compare the X-ray fluorescence spectrum test result of the sample with the X-ray fluorescence spectrum test result of the calibration sample to obtain the calcium ion content in the sample. The difference between the two calcium ion content results repeatedly measured by the same operator for the same batch of lime powder to be tested is not greater than 10% of the arithmetic mean value. The final content of this batch is 94.76%.
[0038] Example 2 Another batch of limestone raw materials was selected and tested in the same manner as in Example 1, except that: S2 started with 11.0 g of pressed raw material and gradually decreased. The results are shown in Table 1.
[0039] Table 1
[0040] Among them, the crack-free specimens are Figure 2 As shown in Figure 2, the cracked specimens Figure 3 shown.
[0041] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for determining the calcium ion content in lime powder, characterized in that the steps include: S1, preparing lime powder to be tested with set fineness; S2, use lime powder to be detected to suppress the sample, when cracks occur, gradually reduce the weight of lime powder to be detected for sample preparation and test compression, until the test compression does not produce cracks for many times, the powder consumption that does not produce cracks is determined as the weighing weight of powder to be detected, and the lime powder used to determine the calcium ion concentration is used to prepare the calibration sample in the same way; S3, correcting the calibration parameter values in the detection system, and performing X-ray fluorescence spectrum detection on the sample; S4. Compare the X-ray fluorescence spectrum detection result of the sample with the X-ray fluorescence spectrum detection result of the calibration sample to obtain the calcium ion content in the sample.
2. The method for determining the calcium ion content in lime powder as claimed in claim 1, wherein: In S1, the fineness of the lime powder is 0.08 mm square hole sieve and more than 90% of it passes through the sieve.
3. The method for measuring calcium ion content in lime powder as claimed in claim 1, characterized in that: In S2, the pressure of the pressed sample is a set value, and the pressure of the pressed sample of the lime powder to be tested is the same as that of the calibration sample.
4. The method for measuring calcium ion content in lime powder as claimed in claim 1, wherein: In S2, the method of reducing the weight of lime powder used for sample preparation and conducting trial pressing is: each time the amount of lime powder is reduced by 0.08 to 0.1 g, the trial pressing is performed 5 to 6 times.
5. The method for measuring calcium ion content in lime powder as claimed in claim 1, wherein: The criterion for judging whether cracks are not generated is that the pressed sample does not protrude from the end face of the steel ring, the sample is removed after pressing, and after the floating powder of the sample is blown off, the tested surface and back face are flat and free of cracks.
6. The method for measuring calcium ion content in lime powder as claimed in claim 1, wherein: In S3, the calibration parameter values in the system are constants determined by a large number of calibration processes.
7. The method for determining the calcium ion content in lime powder as claimed in claim 1, wherein: In S4, the powder fineness of the calibration sample is the same as that of the lime powder.
8. The method for determining the calcium ion content in lime powder as claimed in claim 1, wherein: Optionally, in S4, the weight of the calibration sample is consistent with the weighed weight of the powder to be tested.
9. The method for determining the calcium ion content in lime powder as claimed in claim 1, wherein: In S4, the difference between two calcium ion content results repeatedly measured by the same operator for the same batch of lime powder to be tested is not greater than 10% of their arithmetic mean.
10. The method for determining the calcium ion content in lime powder as claimed in claim 1, wherein: If the sample does not crack, select high pressure.